Should I trust you? Learning and memory of social interactions in dementia. (September 2017) - Wong, Stephanie; Irish, Muireann; O'Callaghan, Claire; Kumfor, Fiona; Savage, Greg; Hodges, John R.; Piguet, Olivier; Hornberger, Michael
Abstract: Social relevance has an enhancing effect on learning and subsequent memory retrieval. The ability to learn from and remember social interactions may impact on susceptibility to financial exploitation, which is elevated in individuals with dementia. The current study aimed to investigate learning and memory of social interactions, the relationship between performance and financial vulnerability and the neural substrates underpinning performance in 14 Alzheimer's disease (AD) and 20 behavioural-variant frontotemporal dementia (bvFTD) patients and 20 age-matched healthy controls. On a "trust game" task, participants invested virtual money with counterparts who acted either in a trustworthy or untrustworthy manner over repeated interactions. A non-social "lottery" condition was also included. Participants' learning of trust/distrust responses and subsequent memory for the counterparts and nature of the interactions was assessed. Carer-rated profiles of financial vulnerability were also collected. Relative to controls, both patient groups showed attenuated learning of trust/distrust responses, and lower overall memory for social interactions. Despite poor learning performance, both AD and bvFTD patients showed better memory of social compared to non-social interactions. Importantly, better memory for social interactions was associated with lower financial vulnerability in AD, but not bvFTD. Learning and memory of social interactions was associated with medial temporal and temporoparietal atrophy in AD, whereas a wider network of frontostriatal, insular, fusiform and medial temporal regions was implicated in bvFTD. Our findings suggest that although social relevance influences memory to an extent in both AD and bvFTD, this is associated with vulnerability to financial exploitation in AD only, and is underpinned by changes to different neural substrates. Theoretically, these findings provide novel insights into potential mechanisms that give rise to vulnerability in people with dementia, and open avenues for possible interventions. Highlights: Susceptibility to financial exploitation is elevated in individuals with dementia. Learning and memory of social interactions may impact on financial exploitation. Learning and memory of social interactions were affected in bvFTD and AD. Memory of social interactions related to financial exploitation in AD only. Social learning and memory relates to divergent neural substrates in bvFTD and AD.